The creation of the 9/11 myth and its ritualisation inside New York City. - Šubrt, Oldřich (Social Identities, 2025)
The paper examines the creation of the 9/11 myth and its subsequent ritualisation. Using Lévi-Strauss' methodology, the analysis reveals the ideological mediator: a call for paternalistic governance aimed at peace and security through military operations bringing order and justice. The tabooing function of the mediator, ritually re-enacted during Patriot Day, is highlighted through the application of theories of analytical psychology. Through ritualisation, the terror of the United States in the Middle East was tabooed and pushed into the collective unconsciousness, leaving the disintegrated post-9/11 identity to externalise its distress in domestic and foreign terrorist acts that continue to this day.